1985
DOI: 10.1677/joe.0.1050163
|View full text |Cite
|
Sign up to set email alerts
|

The priming effect of LH-releasing hormone: effects of cold and involvement of new protein synthesis

Abstract: The possible involvement of protein synthesis in the priming effect of LH-releasing hormone (LHRH) has been investigated in vitro using hemipituitary glands from pro-oestrous rats. Cycloheximide (7.1 mumol/l) blocked the priming effect of LHRH (elicited by 8.5 nmol LHRH/l) and protein synthesis (assessed by gel electrophoresis of 35S-labelled pituitary proteins). Pituitary glands were also incubated at 0-1 degrees C followed by incubation at 37 degrees C. While incubation at 0 degrees C for either 1 or 2 h red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…There are major differences between the priming and the releasing action of LHRH (Fink et al 1982a), the most prominent of which is that the priming but not the releasing action of LHRH involves the synthesis of a new protein and depends upon the integrity of microfilaments. The new protein synthesized as part of LHRH priming has a molecular mass of about 70 kDa (Curtis, Lyons & Fink, 1985;Fig. 19) and might be similar to the oestrogen-stimulated protein recently discovered by Mobbs, Harlan, Burrows & Pfaff (1988) in the hypothalamic ventromedial nucleus and in the mid-brain central grey.…”
Section: Rapid Effects Of Steroidsmentioning
confidence: 65%
“…There are major differences between the priming and the releasing action of LHRH (Fink et al 1982a), the most prominent of which is that the priming but not the releasing action of LHRH involves the synthesis of a new protein and depends upon the integrity of microfilaments. The new protein synthesized as part of LHRH priming has a molecular mass of about 70 kDa (Curtis, Lyons & Fink, 1985;Fig. 19) and might be similar to the oestrogen-stimulated protein recently discovered by Mobbs, Harlan, Burrows & Pfaff (1988) in the hypothalamic ventromedial nucleus and in the mid-brain central grey.…”
Section: Rapid Effects Of Steroidsmentioning
confidence: 65%
“…It is interesting to note here that the self-priming (sensitization) effect of luteinizing hormone-releasing hormone (LHRH) in pituitary tissue displays similar features to AVP sensitization in the brain in that pre-exposure of pituitary tissue to LHRH cause a potentiation of LHRH-induced inositol phosphate accumulation with no corresponding alterations in LHRH receptor number or affinity (35). Furthermore, evidence was provided that the facilitated secretory responses to LHRH caused by pre-exposure of pituitary tissue to LHRH appear to depend upon protein synthesis (36)(37)(38), and recently Mobbs et al (39,40) have shown the newly synthesized protein associated with enhanced LHRH responses to be an isozyme of the phospholipase C family known to be involved in PI hydrolysis. Thus, our findings and those of others suggest that the regulatory mechanism(s) underlying AVP sensitization in the brain may be similar to those underlying LHRH-induced self-priming in the pituitary.…”
Section: Discussionmentioning
confidence: 99%
“…The ovarian protein factor was called gonadotropin surge-inhibiting factor (GnSIF) (14). Many studies have been devoted to the mechanisms involved in the self-priming action of GnRH (15)(16)(17)(18)(19)(20), but relatively few studies have addressed the question of how a suppressive feedback mechanism is established at the pituitary level. Recently, it was suggested that inter¬ cellular communication involving different pituitary cell types may well play a role in the establishment of a biphasic LH secretion response to GnRH (21).…”
mentioning
confidence: 99%